1974
DOI: 10.1021/ac60340a024
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric determination of N-arylhydroxylamines with 9-chloroacridine

Abstract: sis. SRM paint was analyzed by polarography and atomic absorption. The reasonably good agreement between 252Cf activation analysis and the other methods demonstrates the reliability and utility of the isotope source technique for this determination.Irradiation for 2 hours with the 600-Mg 252Cf source followed by 100 minutes of counting with a 60-cm3 Ge(Li) detector yields about 7 counts of the 204>«Pb isotope per milligram of lead. For a paint sample weighing 1.5 grams, the lower limit of determination would b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1975
1975
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 12 publications
(3 reference statements)
1
0
0
Order By: Relevance
“…The colour produced from the reaction of hydrolyzed paracetamol with 9-CA suggested that a free amino function in the molecule is necessary for the reaction. This finding is in agreement with the reaction of primary aromatic amines and/or aromatic hydroxylamine's with the acridine (Gammans et al, 1974;Stewart and Lotti, 1970;Shaw et al, 1969;Ray et al, 1969) to form highly coloured solutions. However, the reaction mechanism has been explained in Scheme (1).…”
Section: Nature Of the Coloured Product And Stability Constantsupporting
confidence: 82%
“…The colour produced from the reaction of hydrolyzed paracetamol with 9-CA suggested that a free amino function in the molecule is necessary for the reaction. This finding is in agreement with the reaction of primary aromatic amines and/or aromatic hydroxylamine's with the acridine (Gammans et al, 1974;Stewart and Lotti, 1970;Shaw et al, 1969;Ray et al, 1969) to form highly coloured solutions. However, the reaction mechanism has been explained in Scheme (1).…”
Section: Nature Of the Coloured Product And Stability Constantsupporting
confidence: 82%